Efficacy and acceptability of interpersonal psychotherapy for depression in adolescents: A meta-analysis of randomized controlled trials. (July 2017) - Pu, Juncai; Zhou, Xinyu; Liu, Lanxiang; Zhang, Yuqing; Yang, Lining; Yuan, Shuai; Zhang, Hanpin; Han, Yu; Zou, Dezhi; Xie, Peng
Abstract: In this study, we evaluate the efficacy and safety of interpersonal psychotherapy (IPT) for adolescents with depression. We searched our existing database and electronic databases, including PubMed, Cochrane, EMBASE, PsycINFO, Web of Science, and CINAHL databases (from inception to May 2016). We included randomized controlled trials comparing IPT with various control conditions, including waitlist, psychological placebo, treatment as usual, and no treatment, in adolescents with depression. Finally, we selected seven studies comprising 538 participants comparing IPT with three different control conditions. Pooled analyses suggested that IPT was significantly more effective than control conditions in reducing depressive symptoms at post-treatment and follow-up, and increasing the response/remission rate at post-treatment. IPT was also superior to control conditions for all-cause discontinuation and quality of life/functioning improvement outcomes. However, there was no evidence that IPT reduces the risk of suicide from these data. Meta-analysis demonstrated publication bias for primary efficacy, while the adjusted standardized mean difference using the trim-and-fill method indicated IPT was still significantly superior to the control conditions. Current evidence indicates IPT has a superior efficacy and acceptability compared with control conditions in treating adolescents with depression. Highlights: Meta-analysis of controlled trials for IPT in adolescents with depression. IPT has superior efficacy and acceptability in adolescents with depression. IPT is a useful strategy to improve quality of life/functioning.